Pergantian Manajemen dan Opini Auditor Serta Pengaruhnya Terhadap Pergantian Auditor - Isnaeni Isnaeni (BJRM (Bongaya Journal of Research in Management), 2021)
Abstract: This study aims to examine the effect of audit opinion and management turnover on auditor turnover because the results of previous studies have different empirical results. The source of data used in this study is secondary data, namely the annual report of manufacturing companies in the food and beverage sub-sector which is accessed through www.idx.co.id. The number of population sampled in this study were 13 companies with 3 years of observation. Determination of the sample using purposive sampling method. The regression used in this study uses logistic regression analysis. The results showed that the variables of audit opinion and management change had no effect on auditor auditor change.